Protein Tyrosine Nitration in Lung Cancer: Current Research Status and Future Perspectives - Zhan, Xianquan; Huang, Yuda; Qian, Shehua (Current Medicinal Chemistry, 2018)
Oxidative/nitrative damage is a crucial element among the complex factors that contribute to lung carcinogenesis. Nitric oxide (NO) free radicals, through chemical modifications such as tyrosine nitration, are significantly involved in lung carcinogenesis and metastasis. NO-mediated protein nitration, which is the addition of the nitro group (–NO2) to position 3 of the phenolic ring of a tyrosine residue, is an important molecular event in lung cancer, and has been studied with mass spectrometry. Nitration is involved in multiple biological processes, including signal transduction, protein degradation, energy metabolism, mitochondrial dysfunction, enzyme inactivation, immunogenic response, apoptosis, and cell death. This article reviews the relationship of NO and its derivates and lung cancer, formation and roles of tyrosine nitration in lung cancer, differences of protein nitration between lung cancer and other inflammatory pulmonary diseases, current status of protein nitration and nitroproteomics in lung cancer, and future perspectives to achieve a better understanding of lung carcinogenesis, for biomarker discovery; and for new diagnostic and prognostic monitoring, and therapeutic targets.
Keywords: Lung cancer